Induction of protein conformational change inside the charged electrospray droplet. (29th January 2013) - Banerjee, Shibdas
<x xml:space="preserve">Abstract</x> The behavior of the analyte molecules inside the neutral core of the charged electrospray (ES) droplet is not unambiguously known to date. The possibility of protein conformational change inside the charged ES droplet has been investigated. The ES droplets encapsulating the protein molecules were exposed to the acetic acid vapor in the ionization chamber to absorb the acetic acid vapor. Because of the faster evaporation of water than that of acetic acid, the droplets became enriched with acetic acid and thus altered the solvent environment (e.g. pH and polarity) of the final charged droplets from where the naked charged analytes (proteins) are formed. Thus, the perturbation of the ES droplet solvent environment resulted in the protein conformational change (unfolding) during the short lifespan of the ES droplet and that is reflected by the multimodal charge state distribution in the corresponding mass spectra. Further, the extent of this conformational change inside the ES droplet was found to be related to the structural flexibility of the protein. Although the protein conformational change inside the ES droplet has been driven by using acetic acid vapor in the present study, the results would help in the near future to understand the spontaneity of the conformational change of the analyte on the millisecond timescale of phase transition in the natural way of ES process. Copyright © 2013 John Wiley & Sons, Ltd.